Immunolocalization of different neuropeptides in human interthalamic adhaesion indicates its functionality - Puškaš, Laslo; Malobabić, Slobodan; Lazić, Dijana; Todorović, Vera; Aksić, Milan; Filipović, Branislav (Vojnosanitetski pregled, 2014)
Background/Aim. The interthalamic adhaesion (IA), gray matter connecting both thalami, is absent in about a quarter of human brains. Controversies are present about the nature and functional significance of the human IA. Methods. In six adult human brains we investigated the expression of different neuropeptides: somatosatin (SOM), neuropeptide Y (NPY), ghrelin, neurotensin (NT), adrenocorticotropic hormone (ACTH), substance P (SP) and L-enkephalin (L-Enk) in neurons and/or neuropil of the IA, using immunohistochemistry (streptavidin-biotin technique). Results. In neurons, as well as in fibers, we found immunoreactivity for ghrelin, SOM, L-Enk and NT. However, reactivity for NPY, SP and ACTH was present only in fibers within the IA. Fusiform neurons were immunoreactive for SOM, Ghrelin, L-Enk, and NT, neurons with oval perikaryon for SOM, and L- Enk, triangular neurons showed immunoreactivity mainly for NT and multipolar neurons for NT and L-Enk. Conclusion. These findings can contribute to the understanding of the function of interthalamic adhaesion, and to resolving the question whether it is a vestigial structure. No mather if the interthalamic adhaesion is vestigial structure or not, its presence or absence could be a marker for other, genetic or functional differences between human brains. Our findings indicate the presence of certain neuronal organization in the human interthalamic adhaesion which could have functional significance, and do not support its vestigial nature.